A Comparative Study: Similarities and Differences between Indonesia’s Curriculum and Philippine’s Curriculum - Agus Nasir; Hendri Yawan; Saifullah Saifullah (LPPPIPublishing, 2022)
The school curriculum of Indonesia has changed three times over the same period since 2004. Meanwhile the new curiculum of Philippine was changed in 2012. This study attempted to compare Indonesia 2013 curriculum (K13) with Philippine curriculum K to 12 (K12) regarding their development and enacment while also uncovering the embedded cultural values and influences on both curricula. The discussion also tried to investigate how the two curricula have impacted different stakeholders involved. This research was conducted by reviewing the collated official curriculum documents published by education ministry of the two countries and analysing facts and issues emerged from related studies and articles. The study reveals that the similarity of both curricula reforms lies at the fact that both curricula are deliberately reformed in response to the actual needs of society in each country. Meanwhile, the difference might be seen from the lens of curricula purposes in which K13 was designed to strengthen social and religious values while K-12 was focused on the development of knowledge and skills. The findings suggest that Indonesian curriculum needs to be made more practical instead of being too philosophical while gradual and continuous evaluation in necessary aspects is more recommended than total reforms which tend to result in longer adaptation and transition process.